2008
DOI: 10.1007/s11274-008-9830-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of ergosterol peroxide from Nomuraea rileyi infected larvae of tobacco cutworm

Abstract: In the search for potential cytotoxic substances produced by Nomuraea rileyi, an active compound was isolated from mycosed insects through an activity guided fractionation process. The compound, cytotoxic against the Sf9 insect cell line, was identified to be ergosterol peroxide (5a, 8a-epidioxy-24(R)-methylcholesta-6, 22-dien-3b-ol) using nuclear magnetic resonance techniques, infrared spectrometry, and mass spectroscopy. Anticancer screens demonstrated that ergosterol peroxide at micromolar concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
4
5
0
Order By: Relevance
“…Accordingly, it upregulates the oxidative, stress-sensitive responsible genes and downregulates the STAT1 and interferon-inducible genes by increasing the intracellular levels of ROS [23]. Similarly, the anticancer activity of EP is in good agreement with previously published findings on the inhibition of cancer cell proliferation [24].…”
Section: Discussionsupporting
confidence: 73%
“…Accordingly, it upregulates the oxidative, stress-sensitive responsible genes and downregulates the STAT1 and interferon-inducible genes by increasing the intracellular levels of ROS [23]. Similarly, the anticancer activity of EP is in good agreement with previously published findings on the inhibition of cancer cell proliferation [24].…”
Section: Discussionsupporting
confidence: 73%
“…and its activity against B. tabaci are in accordance with the ndings of R.M. Zolotar et al Similar results on insecticidal activity of ergosterol peroxide isolated from Nomuraea rileyi against tobacco cutworm were documented by Pannipa Prompiboon et al 32 who reported the moderate effects such as 46.7 % mortality was caused against Spodoptera litura larvae via topical application at an interval of one week with 90-120 µg / insect, whereas, our research results showed 38.33 % mortality at 72 h exposure at concentration of 50 ppm on B. tabaci. Additional biological activities of compounds ergosterol peroxide include antioxidant activities 33 , antimycobacterial activities 34 in ammatory activities 35 .…”
Section: Discussionsupporting
confidence: 89%
“…However, S. cosmiodes has not been reported as a natural host for N. rileyi (Sosa-Gomez & Silva 2002) and it is not affected by the fungi at the different larval developmental stages. This fact leads to speculate that the presence of the well-known antioxidant vitamin E can be involved in S. cosmioides natural resistance towards the fungus, as one of the proposed mechanisms of N. rileyi pathogenicity is the breakdown of the larval cuticle through the generation of ergosterol peroxide (Prompiboon et al 2008). On the other hand, lack of vitamin E within the cuticle could explain the susceptibility of A. gemmatallis larvae to N. rileyi.…”
Section: Resultsmentioning
confidence: 99%